A History of the American Worker - Morris, Richard B. (Richard Brandon), 1904-1989 (Book collections on Project MUSE., 1983)
Offering the six historical essays from the out-of-print Bicentennial volume originally published by the U.S. Department of Labor, this book tells the richly dramatic and rewarding story of the working men and women who built the nation, from colonial settlement and the beginning of the republic through the modern labor movement and the space age. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.